I will help you solve this equation.
Given: -x = √(2x + 15)
Square both sides to eliminate the square root:
(-x)^2 = (√(2x + 15))^2
x^2 = 2x + 15
Rearrange the equation to a quadratic form:
x^2 - 2x - 15 = 0
Factor the quadratic equation:
(x - 5)(x + 3) = 0
Set each factor to zero and solve for x:
x - 5 = 0
x = 5
x + 3 = 0
x = -3
Therefore, the solutions to the equation are x = -3 and x = 5.
The correct answers are:
A. -5
B. -3
C. 3
D. 5
So the correct answer is B. -3
solve. -x=the square root of 2x+15
A. -5
B. -3
C. 3
D. 5
1 answer